THE MENA REGION: A GREAT POWER COMPETITION - Karim Mezran (Pubblicazioni ISPI, 2019)
The volume deals with competition among regional and external players for the redistribution of power and international status in the Middle East and North Africa, with a focus on Russia's renewed role and the implications for US interests. Over the last few years, a crisis of legitimacy has beset the liberal international order. In this context, the configuration of regional orders has come into question, as in the extreme case of the current collapse in the Middle East. The idea of a "Russian resurgence" in the Middle East set against a perceived American withdrawal has captured the attention of policymakers and scholars alike, warranting further examination. This volume, a joint publication by ISPI and the Atlantic Council, gathers analysis on Washington's and Moscow's policy choices in the MENA region and develops case studies of the two powers' engagament in the countries beset by major crises.